Histo-Morphological Comparison of Placental Adaptations in Normal and Gestational Diabetes Mellitus Pregnancies and Their Impact on Neonatal Outcomes - Amit K. Yadav; Sunita Yadav; Kaweri Dande; Vijayta Singh; Indra Kumar; Richa Yadav (Journal of Pharmacy and Bioallied Sciences)
Background: Gestational diabetes mellitus (GDM) significantly affects maternal and fetal health by altering placental structure and function, critical for fetal growth. Understanding the histomorphological changes in GDM-affected placentas can offer insight into how these adaptations impact pregnancy outcomes. Materials and Methods: This cross-sectional study examined 220 placental samples (110 from normal pregnancies and 110 from GDM-complicated pregnancies) collected from Index Medical College and Hospital. Morphological characteristics (shape, cotyledon count, cord insertion type), morphometric measurements (diameter, thickness, circumference, weight), and histological markers (syncytial knots, fibrinoid necrosis, villous fibrosis, and perivillous fibrin deposition) were assessed. Neonatal outcomes, including birth weight, APGAR scores, and fetoplacental weight ratio, were recorded and statistically analyzed. Results: Placentas from GDM pregnancies showed significantly higher weight (556.1 g vs. 498.8 g, P < 0.05), thickness, and cotyledon count (13 vs. 9, P < 0.05). GDM was associated with a predominance of eccentric cord insertions (71.8% vs. 27.3% in normal, P < 0.05) and diverse placental shapes. Histologically, GDM placentas had elevated syncytial knots (100%), fibrinoid necrosis (83.6%), and villous fibrosis (70.9%), suggesting placental stress and reduced efficiency. Neonates from GDM pregnancies had higher birth weights (3.68 kg vs. 3.2 kg, P < 0.001) and a lower fetoplacental weight ratio, highlighting the risks of fetal macrosomia. Conclusion: The observed histomorphological changes in GDM placentas suggest compensatory mechanisms in response to the hyperglycemic environment but may also contribute to neonatal complications.